Development of “Trade War” Business Simulation Educational Game Using Unity - Mulyadi Kamsul; Aina Damayunita; Rifqi Syamsul Fuadi (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect of learning media business simulation educational game "Trade War" on students' interest and understanding of business at SD Kristen Rehoboth Elementary School. Schools generally only use learning media in the form of books and teacher explanations which only aim to ensure students pass the written test so that student motivation and learning outcomes are low because they are just memorizing without understanding the material, while the business subject itself is difficult to understand only through books. Business simulation educational games allow students to interact directly with the business environment and understand the subject matter to be able to apply it in the real world. This study uses research and development methods with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. Research data was collected by distributing validation questionnaire sheets to four validators to give validation values on material aspects and media aspects and distributing response questionnaires to 30 students to assess the validity of aspects of the benefits of learning media on students' business interests and understanding. The results of the study show that the learning media for the business simulation educational game "Trade Wars" for fourth grade elementary school students is quite valid from the aspects of material, media, and benefits for students.